Taxonomic notes on Alpheus inopinatus Holthuis & Gottlieb, 1958 and Alpheus cf. lobidens De Haan, 1849 from Kuwait (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur; Al-Kandari, Manal; de Grave, Sammy (Zootaxa, 2020)
The status of the common intertidal snapping shrimp, Alpheus inopinatus Holthuis & Gottlieb, 1958, is discussed based on newly collected material from Kuwait. Alpheus inopinatus was previously confused with morphologically very similar species in the Alpheus lobidens De Haan, 1849 species complex, formerly identified as A. crassimanus Heller, 1862 and herein tentatively referred to as A. cf. lobidens. The material herein examined strongly supports the validity of A. inopinatus based on several morphological characters, as well as differences in the colour pattern, compared to other members of the A. lobidens complex.